Synthesis of indium and lead phthalocyanine as photocatalysts for photodynamic antimicrobial chemotherapy and photo-oxidation of pollutants - Osifeko, Olawale L (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
This thesis explores the synthesis of metallophthalocyanines as potential photosensitizers for application in photodynamic antimicrobial chemotherapy and phototransformation of environmental pollutants. The metallophthalocyanines containing amino substituent were conjugated with magnetic nanoparticle and semiconductor quantum dots via an amide bond and by chemisorption onto gold nanoparticles surface. Techniques such as time-resolved fluorescence measurements, transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), elemental analysis, fourier transform infrared (FTIR), nuclear magnetic resonance (¹H, ¹³C, and cozy of symmetrical phthalocyanine), electronic spectroscopy, as well as mass spectroscopy were employed to characterize all metallophthalocyanines. Quarternized pyridyloxy substituted phthalocyanine and asymmetric (AB3) metallophthalocyanines were embedded in electrospun polystyrene fiber. General trends are described for quantum yields of fluorescence, triplet, singlet oxygen and photodegradation as well as lifetimes of fluorescence and triplet state of the compounds. There is an increase in triplet quantum yield for Pcs in the presence of gold nanoparticles (AuNPs) and semiconductor quantum dots (QDs), but not in the presence of magnetic nanoparticles (MNPs). Photodynamic inactivation of Escherichia coli with the quarternized photosensitizers at low concentrations totally inactivate the bacteria compared to non-charged photosensitiser. Also, a similar trend was observed for the magnetic nanoparticles conjugates. Photooxidations of bisphenol A and 4-chlorophenol were carried out in this study using two asymmetric Indium(III) phthalocyanines photosensitizers. The photooxidation reactions were compared with those of a symmetrical indium(III) phthalocyanines containing four quaternized 4-pyridyloxy substituents. The complexes were embedded in electrospun polystyrene fiber for heterogeneous photocatalysis. The immobilized photosensitizers possess good singlet oxygen generation potentials in aqueous media. The asymmetrical phthalocyanine containing 4-pyridylsulfanyl and one aminophenoxy showed the best photocatalytic behavior.
Keywords: Uncatalogued